The Improvement Of Student Achievement In Writing Skill By Applying Think Talk Write Strategy At MTs Nurul Qur’an - Ika Susanti (International Journal of Educational Research, 2024)
Mastering writing skill is difficult for new learner of English. This paper focuses on analyzing the use of TTW (think talk write) strategy in enhancing students’ achievement in writing a greeting dialogue. The research was conducted in MTs Nurul Al-Qur'an Jombang. It involved first grade students that consist of 40 students. Action research design was used in conducting this research. The results showed that the use of TTW strategy in teaching writing skill can enhance students achievement in writing skill. The final score of students showed that they got a higher score in writing after applying this theory. Furthermore, based on the questionnaires results show that by using this theory in teaching writing students can enjoy and understand the material well. Junior High School students find it difficult to master the ability to write English. This paper focuses on analyzing the use of TTW strategy in improving students ability to write a dialogue about greeting. This study was conducted at MTs Nurul Al-Qur'an Jombang and involved 40 first graders. Class action research is the design used in this research. The results of this research indicate that the use of TTW strategy in teaching menuis can improve students ' ability to write. Furthermore, based on the results of the questionnaire showed that the use of this theory in learning to write can help students to enjoy the learning process and understand the material well.